Sub-micron microparticles with tunable fluorescence emission obtained via co-self-assembly of amidoximed polymeric ligands and lanthanide ions - Qiu, Huandi; Ran, Qimeng; Bai, Yun; He, Wei; Zheng, Li; Pan, Cong; Jia, Kun; Hu, Yiguo (Frontiers in Chemistry, 2023)
Lanthanide coordinating polymeric microparticles have witnessed increasing research interests during the past decades due to their versatile morphology and tunable fluorescent properties. Herein, we have synthesized an amidoximed block copolymer containing aromatic backbone and pendent amidoxime as well as carboxyl groups, which has been employed as the ligand to sensitize the intrinsic fluorescence emission of lanthanide ions of Tb3+ and Eu3+. Furthermore, the lanthanide coordinating polymeric microparticles showing tunable green and red emission fluorescence have been prepared via the emulsion confinement co-self-assembly of amidoximed polymeric ligands with Tb3+ or Eu3+. It is found that both the fluorescence emission and sizes of obtained fluorescent microparticles can be easily modulated in a wide range by tuning concentration of polymers and lanthanide ions, as well as emulsion evaporation temperature. Thanks to their tunable sizes (250-900 nm), fluorescence emission as well as presence of surface active functional groups, the present fluorescent microparticles would find potential applications in in-vitro detection, optical encoding and devices.